2015
DOI: 10.1261/rna.048843.114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nucleosome positioning and progesterone-induced alternative splicing in breast cancer cells

Abstract: Splicing of mRNA precursors can occur cotranscriptionally and it has been proposed that chromatin structure influences splice site recognition and regulation. Here we have systematically explored potential links between nucleosome positioning and alternative splicing regulation upon progesterone stimulation of breast cancer cells. We confirm preferential nucleosome positioning in exons and report four distinct profiles of nucleosome density around alternatively spliced exons, with RNA polymerase II accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Two recent studies assessed the relationship between nucleosome occupancy and alternative splicing. One study found that near alternative exons that are preferentially included in progesterone treated breast cancer cells, the chromatin structure switched from poorly positioned to well-positioned nucleosomes and this rearrangement correlated with increased pol II occupancy consistent with pausing 96 . A second study addressed whether changes in nucleosome occupancy can cause changes in splice site selection by restricting the histone supply in colon carcinoma cells through inhibition of histone mRNA 3’ end formation.…”
Section: Kinetic Coupling: How Elongation Rate Affects Nascent Pre-mrmentioning
confidence: 99%
“…Two recent studies assessed the relationship between nucleosome occupancy and alternative splicing. One study found that near alternative exons that are preferentially included in progesterone treated breast cancer cells, the chromatin structure switched from poorly positioned to well-positioned nucleosomes and this rearrangement correlated with increased pol II occupancy consistent with pausing 96 . A second study addressed whether changes in nucleosome occupancy can cause changes in splice site selection by restricting the histone supply in colon carcinoma cells through inhibition of histone mRNA 3’ end formation.…”
Section: Kinetic Coupling: How Elongation Rate Affects Nascent Pre-mrmentioning
confidence: 99%
“…It has been proposed that this exon-dependent RNAPII accumulation might be influenced by chromatin, because increased nucleosome occupancy has been found at exons as compared with surrounding introns (19,20). Recently, progesterone-dependent nucleosomal changes have been shown to correlate with changes in alternative splicing (21). In addition, some histone posttranslational modifications associated with elongation are enriched in exons.…”
mentioning
confidence: 99%
“…As a matter of fact, SRSF2 is known to play an active role in transcriptional elongation by facilitating RNA polymerase II pause release (Lin et al 2008;Ji et al 2013) and SRSF2-mediated enhanced elongation rates could indeed promote exon skipping by facilitating kinetic competition between alternative sites (Dujardin et al 2013). Nucleosome positioning was also proposed to influence RNA polymerase II elongation rates and AS (Schwartz and Ast 2010;Gómez et al 2013;Iannone and Valcárcel 2013;Iannone et al 2015) and it is interesting, in this regard, that several members of the family of chromatin-associated High-Mobility Group (HMG) proteins were identified in our proteomic analysis. HMGA1 was enriched in C-rs3736234 RNA and knock down of HMGA1 increased OLR1 exon 5 inclusion specifically in the C-rs3736234 minigene.…”
Section: Discussionmentioning
confidence: 93%